The evolutionary approach to entropy: Reconciling Georgescu-Roegen's natural philosophy with the maximum entropy framework - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2010)
In Georgescu-Roegen's classical, though controversial discussion of entropy in relation to economics, the dualism of mechanical and subjective time plays a pivotal role. I argue that this fundamental distinction also inheres modern approaches to maximum entropy. Following Searle, I introduce the ontological dualism of observer independent and observer relative facts, and show that the notion of entropy also manifests this dualism, in the sense of the contextuality of measurements in experimental settings. Extending on the notion of observer relativity, I argue that the MaxEnt principle can be generalized into a framework of analyzing the evolution of (biological, technological etc.) functions under natural selection, if functions are equated with inference devices. Then, observer relativity is function relativity. In hierarchical evolutionary systems, this corresponds to the Maximum Entropy Production Principle, in the sense that functional evolution approximates gradients of maximum dissipation of energy. Against this background, the Georgescu-Roegen dualism of time translates into the dualism of observer independent entropy, which is the object of MEPP, and observer relative entropy, which is the object of MaxEnt. Both are two aspects under which evolution in general and economic evolution in particular can be analyzed.
Keywords: B52; Q57; 330; Georgescu-Roegen; maximum entropy; observer relativity; time; hierarchical evolutionary systems; natural selection; physical concepts of information